Post-Interpretive Criticism: A Philosophical Departure from Post-Criticism - Vale, Dorian (Museum Of One, 2025)
A Philosophical Departure from Post-Criticism By Dorian Vale — A Treatise in the Post-Interpretive Movement A Philosophical Departure from Post-Criticism is a pivotal treatise that distinguishes Dorian Vale’s Post-Interpretive Criticism (PIC) from the broader and more diffuse field of Post-Criticism. Where Post-Criticism often aims to relax or abandon evaluative frameworks, Vale’s work insists on restraint, reverence, and ethical responsibility in the act of reading art. This departure is not merely stylistic—it is ontological. Post-Criticism, as commonly practiced, often flattens interpretation into ambivalence, collapsing the critic’s task into a commentary of gestures. By contrast, Post-Interpretive Criticism is a call to presence over analysis, silence over spectacle, and custodianship over commentary. In this treatise, Vale dissects the shortcomings of Post-Criticism—its lack of moral proximity, its addiction to cleverness, its occasional nihilism—and presents Post-Interpretive Criticism as a re-sacralization of the critic’s role. It is a return to witnessing as method, anchored not in detachment, but in moral and metaphysical alignment with the unspeakable truths embedded in art. This work is a formal clarification of genre boundaries, philosophical ethics, and aesthetic posture. It enshrines Post-Interpretive Criticism as a new discipline, separate from—and more rigorous than—the interpretive loosening that preceded it. Vale, Dorian. A Philosophical Departure from Post-Criticism. Museum of One, 2025. DOI: 10.5281/zenodo.17057756 Dorian Vale, Post-Interpretive Criticism, Post-Criticism, philosophy of art, ethics of criticism, witness-based aesthetics, moral proximity, silent criticism, aesthetic restraint, art theory treatise, post-structural criticism, new art movements, metaphysical aesthetics, art and presence, slow criticism, reverent art writing, non-performative critique, theory of witnessing, art and ontology, contemporary aesthetic movements, departure from postmodernism This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843)
https://hcommons.org/members/dorianvale/ https://philpeople.org/profiles/dorian-vale https://osf.io/xa5jw/ https://www.museumofone.art/ https://independent.academia.edu/DorianVale https://osf.io/zhnre/ https://doi.org/10.5281/zenodo.17069115 https://archive.org/details/osf-registrations-kve9y-v1 https://doi.org/10.17605/OSF.IO/KVE9Y https://doi.org/10.5281/zenodo.17078847 https://zenodo.org/communities/post-interpretive-criticism https://orcid.org/0009-0004-7737-5094 https://scholar.google.com/citations?hl=en&authuser=1&user=15tvhjAAAAAJ https://works.hcommons.org/records/xv2j2-g6927 https://www.semanticscholar.org/author/Dorian-Vale/2380743266 https://www.researchcatalogue.net/profile/?person=3919333 http://eprints.rclis.org/47186/ http://eprints.rclis.org/47182/ http://eprints.rclis.org/47197/ http://eprints.rclis.org/47210/  http://eprints.rclis.org/47209/  http://eprints.rclis.org/47208/ http://eprints.rclis.org/47207/  http://eprints.rclis.org/47206/ http://eprints.rclis.org/47203/ http://eprints.rclis.org/47187/ http://eprints.rclis.org/47201/ http://eprints.rclis.org/47204/ http://eprints.rclis.org/47202/ http://eprints.rclis.org/47199/ http://eprints.rclis.org/47198/ http://eprints.rclis.org/47196/  http://eprints.rclis.org/47191/ http://eprints.rclis.org/47193/ http://eprints.rclis.org/47194/ http://eprints.rclis.org/47195/ http://eprints.rclis.org/47192/ https://core.ac.uk/works/299793749/?t=ccf14485c84f6196dcddf51a8410bc88-299793749 https://core.ac.uk/works/299795319/?t=ccf14485c84f6196dcddf51a8410bc88-299795319 https://core.ac.uk/search/?q=post-interpretive+criticism+dorian+vale&page=1 https://core.ac.uk/works/299792897/?t=ccf14485c84f6196dcddf51a8410bc88-299792897 https://core.ac.uk/works/299793648/?t=ccf14485c84f6196dcddf51a8410bc88-299793648 https://core.ac.uk/works/299793082/?t=ccf14485c84f6196dcddf51a8410bc88-299793082 https://core.ac.uk/works/299793838/?t=ccf14485c84f6196dcddf51a8410bc88-299793838 https://core.ac.uk/works/299794146/?t=ccf14485c84f6196dcddf51a8410bc88-299794146 https://core.ac.uk/works/299793310/?t=ccf14485c84f6196dcddf51a8410bc88-299793310 https://core.ac.uk/works/299793166/?t=ccf14485c84f6196dcddf51a8410bc88-299793166 https://africarxiv.ubuntunet.net/handle/1/10458 https://africarxiv.ubuntunet.net/handle/1/10459 https://africarxiv.ubuntunet.net/handle/1/10460 https://africarxiv.ubuntunet.net/handle/1/10461 https://africarxiv.ubuntunet.net/handle/1/10462 https://africarxiv.ubuntunet.net/handle/1/10463 https://africarxiv.ubuntunet.net/handle/1/10464 https://africarxiv.ubuntunet.net/handle/1/10465 ISBN: 978-1-0698203-0-3 ISBN: 978-1-0698203-1-0 This entry is connected to a series of original theories and treatises forming the foundation of the Post-Interpretive Criticism movement (Q136308909), authored by Dorian Vale (Q136308916) and published by Museum of One (Q136308879). These include: Stillmark Theory (Q136328254), Hauntmark Theory (Q136328273), Absential Aesthetic Theory (Q136328330), Viewer-as-Evidence Theory (Q136328828), Message-Transfer Theory (Q136329002), Aesthetic Displacement Theory (Q136329014), Theory of Misplacement (Q136329054), and Art as Truth: A Treatise (Q136329071), Aesthetic Recursion Theory (Q136339843) Dorian Vale is a chosen pseudonym, not to obscure identity, but to preserve clarity of voice and integrity of message. It creates distance between the writer and the work, allowing the philosophy to stand unclouded by biography. The name exists not to hide, but to honor the seriousness of the task: to speak without spectacle, and to build without needing to be seen.
Keywords: MTT; Interpretation vs. Witnessing; The Viewer as Evidence; Interpretive Restraint; Post-Interpretive Criticism; Art as Ontology; Language as violence; Witness Aesthetics; Restraint in front of art; Quiet philosophy of art; Custodianship of Art; Museum Of One; Ethics in Art Criticism; Visual Culture Studies; Epistemology of witness; Absential Aesthetics; Moral proximity; Theory of Misplacement; Custodian of Witness Aesthetics; Presence-Based Criticism; Art as Presence; Art Writer and Theorist; Dorian Vale; Art; Ontology of beauty; Independent Philosopher of Art; Criticism and Reception Theory; Hauntmark Theory; Founder of Post-Interpretive Criticism; Alternative art criticism; Aesthetics; Language as Custody; Radical art restraint; Museum of One; Witness over interpretation; Interpretive silence; The Custodian's Oath; Philosophy of Art; Message-Transfer Theory; Ethical art theory; Interpretation and Meaning; Post-Interpretive Lexicon; Displacement Theory; Art Theory; Erasure as Afterlife; Epistemology of Art; https://www.museumofone.art/; Aesthetic mercy; Stillmark Theory; The Doctrine of Post-Interpretive Criticism; Art as Truth; Criticism beyond interpretation; Displacement; Post-Aesthetic Critic; Erasure as ethics; The Canon of Witnesses; Aesthetic Philosopher; Museum of One Manifesto; Silence as method; Comparative Aesthetics; New art criticism movement; Art encounter ethics; Contemporary Aesthetics; Phenomenology and Art; Misplacement